PELEVELAN MODEL MENTAL SISWA DALAM MEMAHAMI PENGGUNAAN KONSEP TEOREMA PHYTAGORAS PADA SISWA SMP - Ninda Sintyah Rachmawati; Junarti Junarti; Anita Dewi Utami (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2019)
A domain of learning, understanding is an absolute prerequisite for improving cognitive abilities. Leveling the mental model of students is one way in which a teacher can review the extent to which students understand based on their respective levels. The purpose of this study was to describe the six degrees of student's mental models in understanding the concept of using the Pythagoras theorem in junior high school students. The method used in this study is a qualitative research method. The subjects in this study amounted to 61 students who were a combination of 30 students of class VIII A and 31 students of class VIII B. The two classes of subjects were taken so that the six levels of the mental model were founded. The sixty-one items test questions were given. Each of the representatives of mental models who found the criteria was selected, namely two students to be interviewed so that 12 students were interview respondents. To ensure the validity of the data, researchers analyzed the data in two ways, namely data source triangulation and method triangulation. The results of the study showed a description of each level of the student's mental model in understanding the concept of using the Pythagoras theorem. Suatudomain belajar, pemahaman merupakan prasyaratan mutlak untuk meningkatkankemampuankognitif. Pelevelan model mental siswa merupakan salah satu cara dimana seorang pengajar dapat meninjau sejauh manakah pemahaman siswa berdasarkan tingkatan masing – masing. Tujuan penelitian ini adalah untuk mendeskripsikan enam level model mental siswa dalam memahami konsep penggunaan teorema pythagoras pada siswa SMP. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif. Subjek dalam penelitian ini berjumlah 61 siswa yang merupakan gabungan dari 30 siswa kelas VIII A dan 31 siswa kelas VIII B. Dua kelas subjek tersebut diambil agar terpenuhi keenam level model mental. Keenam puluh satu subjek tersebut diberikan soal tes, kemudian dipilih masing – masing dari perwakilan model mental yang telah memenuhi kriteria yaitu 2 siswa untuk diwawancarai. Sehingga terdapat 12 siswa yang menjadi respondenwawancara. Untuk memastikan kevalidan data, peneliti menganalisis data dengan dua cara yaitu triangulasi sumber data dan triangulasi metode. Hasil penelitian menunjukkan deskripsi masing - masinglevel model mental siswa dalam memahami konsep penggunaan teorema pythagoras.